Terrorism, asymmetric warfare, and weapons of mass destruction defending the U.S. homeland - Cordesman, Anthony H. (Praeger, 2002)
There is a wide spectrum of potential threats to the U.S. homeland that do not involve overt attacks by states using long-range missiles or conventional military forces. Such threats include covert attacks by state actors, state use of proxies, independent terrorist and extremist attacks by foreign groups or individuals, and independent terrorist and extremist attacks by residents of the United States. These threats are currently limited in scope and frequency, but are emerging as potentially significant issues for future U.S. security. In this comprehensive work, Cordesman argues that new threats require new thinking, and offers a range of recommendations, from expanding the understanding of what constitutes a threat and bolstering Homeland defense measures, to bettering resource allocation and improving intelligence gathering and analysis.